Effect of amlodipin on insulin sensitivity, glucose and lipid metabolism in hypertensive population - Karaca, I; Akbulut, M; Kilicoglu, AE; Ilkay, E; Ozbay, Y; Arslan, N (Medimond S R L, 2001)
[Abstract Not Available]
4th International Congress on Coronary Artery Disease -- OCT 21-24, 2001 -- PRAGUE, CZECH REPUBLIC
Keywords: Resistance; Hypertrophy